Peranan Bisnis Pesantren Dalam Mensejahterakan Ekonomi Santri (Studi Kasus Pondok Fathul Ulum Jombang) - Muhammad Khoirul Umam; Ahmad Ajib Ridlwan (Nomicpedia: Journal of Economics and Business Innovation, 2022)
Santri in empowering and prospering, this research is to find out the role of business in empowering santri and the role of business in the economic welfare of santri. The method used in this research is qualitative with a case study approach. Data collection techniques through Interview, Observation, Documentation, Archive Records, Physical Devices data sources include Caregivers, Administrators and Santri. test the validity of the data Construct Validity, Internal Validity, External Validity and Rability while the data analysis technique uses an analysis that has been modified with the Qur'an and Al-Hadith. The results of the study stated that the role of Islamic boarding schools in empowering students consisted of helping underprivileged students, donations for orphans, helping to supply canteen food to feed students, while the role of business in the economic welfare of students consisted of students not only relying on their parents, students. can help the needs of families and students can relieve the needs of other students